Assessing a multicomponent intervention to improve quality of life in individuals with Long COVID (COVIDL/MIQoL): study protocol for a randomized controlled trial - Morera, Mireia; Arévalo, Antonio; Garriga, Cristina; Corral-Magaña, Marta; García-Arqué, Mari Carmen; Gragea-Nocete, Marta; Pérez Díaz, Cristina; Roca, Ramon; Llistosella, Maria (Frontiers in Public Health, 2025)
IntroductionThe impact of Long COVID on the quality of life of affected individuals is significant, therefore, the aim of this study is to analyse the effectiveness of the multicomponent intervention protocol to improve quality of life in individuals with Long COVID.MethodsA randomized controlled trial with two parallel arms will be conducted. Individuals diagnosed with Long COVID, but without any severe mental disorders, will be recruited. The sample size is estimated to be around 54 participants per group. A psychologist and a physiotherapist will carry out the intervention between January and March 2025. Participants will receive specific training in psycho-education and physical rehabilitation consisting of 18 sessions, to be held twice a week. Data collection will start in January 2025 and will finish in October 2025. Data will be collected: at baseline, before the intervention (T0); after 9 weeks, post-intervention (T1); and after 24 weeks, follow-up (T2), and will assess quality of live, well-being, anxiety, depression resilience, fatigue, and physical activity. An intention-to-treat analysis will be performed and the effect size will be calculated using Cohen’s d. All statistical analyses will be performed using R software version 4.2.2, with a 95% confidence level and a statistical significance level of p < 0.05.Discussion/conclusionThe results will be disseminated to individuals with Long COVID and their families throughout their primary health care center. Healthcare professionals will receive specific training to be able to develop and implement the intervention. In addition, the results will be disseminated to the scientific community via conferences and publications.Clinical trial registrationhttps://register.clinicaltrials.gov/prs/beta/studies/S000ENW100000080/recordSummary, Identifier NCT06492590.